"Pseudogestational Sac" and Other 1980s‐Era Concepts in Early First‐Trimester Ultrasound: Are They Still Relevant Today?. (11th February 2020) - Phillips, Catherine H.; Benson, Carol B.; Durfee, Sara M.; Heller, Howard T.; Doubilet, Peter M.
Abstract : Objectives: To determine whether an intrauterine round or oval fluid collection ("saclike structure") can prove to be either an intrauterine pregnancy or intrauterine fluid in conjunction with an ectopic pregnancy (sometimes termed "pseudogestational sac") and whether ultrasound features, including the presence or absence of an echogenic rim, "double sac sign" (DSS), or "intradecidual sign" (IDS), are helpful for establishing the diagnosis or predicting the prognosis. Methods: We identified all sonograms obtained from women with positive serum human chorionic gonadotropin results at our institution between January 1, 2012, and June 30, 2018, meeting the following criteria: presence of an intrauterine saclike structure without a yolk sac or embryo; no extraovarian adnexal mass; and follow‐up information identifying the location of the pregnancy as intrauterine or ectopic. Study authors reviewed sonograms in all cases and recorded the following information: presence or absence of each of an echogenic rim around the collection, a DSS, and an IDS, as well as the mean sac diameter. The indications for the initial ultrasound examinations were recorded. Results: A total of 649 sonograms met the inclusion criteria. Of these, 598 fluid collections showed an echogenic rim, 182 a DSS, and 347 an IDS (findings not mutually exclusive). In all 649 cases, a subsequent sonogram or other clinical follow‐up confirmed that the patient had an intrauterine pregnancy. That is, none of the fluid collections proved to be a pseudogestational sac. In total, 41.2% were live at the end of the first trimester, and 58.8% miscarried. The prognosis was better in cases with, compared to without, an IDS ( P = .01, χ 2 ), but no ultrasound feature was clinically useful for ruling in or excluding a good prognosis. Conclusions: In a woman with positive human chorionic gonadotropin results and no extraovarian adnexal mass, the ultrasound finding of an intrauterine saclike structure is virtually certain to be a gestational sac. Ultrasound features of the structure are of no diagnostic or clinically useful prognostic value. Concepts introduced 30 to 40 years ago when ultrasound equipment had far lower resolution than currently, including a DDS, an IDS, and a pseudogestational sac, have no role today in assessing early pregnancy.